The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7314/apjcp.2013.14.11.6475
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Expression in Upper Urinary Tract Urothelial Carcinomas: a Taiwan Study

Abstract: Objectives: Glutathione S-transferase (GST) isoenzymes play important roles in resistance to cell apoptosis and carcinogenesis. We aimed to establish the relationship between GST expression and the prognosis of upper urinary tract urothelial carcinoma (UTT-UC) in Taiwan. Methods: This study retrospectively reviewed 46 patients with pathologically confirmed UUT-UC at Kaohsiung Medical University Hospital. In each patient, expression of GSTT1 and GSTP1 was compared between urothelial carcinoma and normal urothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…In comparison to our findings, several studies have reported an upregulated GSTP1 expression which increased gradually with high-grade tumor or invasive-stage and was linked to decreased levels of urothelial cells apoptosis (Chen et al, 2013;Pljesa-Ercegovac et al, 2011;Savic-Radojevic et al, 2007).…”
Section: )contrasting
confidence: 71%
See 2 more Smart Citations
“…In comparison to our findings, several studies have reported an upregulated GSTP1 expression which increased gradually with high-grade tumor or invasive-stage and was linked to decreased levels of urothelial cells apoptosis (Chen et al, 2013;Pljesa-Ercegovac et al, 2011;Savic-Radojevic et al, 2007).…”
Section: )contrasting
confidence: 71%
“…Some studies indicated an overexpression of GSTP1 gene in esophageal cancer (Joshi et al., ), colorectal cancer (Zhang et al., ), renal cancer (Kaprilian et al., ), lung cancer (Yang et al., ), and in BC (Chen et al., ; Pljesa‐Ercegovac et al., ; Savic‐Radojevic et al., ). Other studies showed reduced GSTP1 gene expression in prostate, endometrial, hepatocellular, and ovarian cancers (Chan et al., ; Li et al., ; Lin et al., ; Martignano et al., ; Mian et al., ; Shilpa et al., ; Zelic et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper urinary tract urothelial carcinoma (UTUC) comprises only 5% of all urothelial tumors in Western countries [1], but its incidence is high in Taiwan, with a ratio 3.08:6.72, UTUC to urinary bladder urothelial carcinoma (UBUC) [2]. Despite advances in surgical technique and improved understanding of UC carcinogenesis [37], 5-year survival rates for patients remain suboptimal [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deregulated GSTT1 expression has been observed in some cancers including bladder cancer, breast cancer and glioma (Dialyna et al, 2001;Diedrich et al, 2006;Ha et al, 2011;Chen et al, 2013). A previous study comparing GSTT1 protein levels in paired normal tissue and colorectal and gastric tumors has found a mild decrease in GSTT1 protein levels (de Bruin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%